2008
DOI: 10.1086/592434
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Tuberculosis, and the Paleopathological Record

Abstract: Osseous manifestation of infectious disease is of paramount importance to paleopathologists seeking to interpret ancient health, but the relationships among infectious agent exposure, development of disease, and skeletal involvement are complex. The outcome of an exposure strongly depends on multiple factors, including ecology, diet, nutrition, immune function, and the genetics of pathogen and host. Mycobacterial diseases are often studied in ancient remains but also are especially influenced by these factors;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 94 publications
0
48
0
Order By: Relevance
“…whether they were resistant or not to the bacteria, and will also influence whether bone changes occur, and the diet a person eats is suggested to affect the development of tuberculous bone changes 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…whether they were resistant or not to the bacteria, and will also influence whether bone changes occur, and the diet a person eats is suggested to affect the development of tuberculous bone changes 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Its has been suggested that nutrition may influence the dissemination of tubercle bacilli to the skeleton and the process of the subsequent formation of lesions that are used by palaeopathologists to diagnose the infection 19 . Furthermore, clinical studies have found an association between iron intake and polymorphisms in the iron transporter gene SLC40A1 and an increased risk for TB 24 The impact of rapid and extensive mobility on the spread of disease is also recognised increasingly today as a key risk factor for TB transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, these analyses cannot provide direct information on the intake of individual micronutrients, such as vitamins and minerals, many of which are essential for maintaining basic metabolic function. As such, the identification of specific diseases of poor micronutritional intake in skeletal remains has the potential to contribute significantly to the creation of a holistic portrait of health, resource use, and human‐environmental interactions in the ancient past (Buckley et al, 2014; Snoddy et al, 2017; Stark, 2014; Wilbur, Farnbach, Knudson, & Buikstra, 2008). …”
Section: Scurvy Dietary Diversity and Paleodietary Reconstructionmentioning
confidence: 99%
“…At present, the World Health Organization estimates that approximately one-third of the world's population are infected with the causative organism, Mycobacterium tuberculosis (World Health Organization, 2012). However, only approximately 10% of all individuals infected, most commonly those with lowered immunity, will ever develop active disease (Wilbur et al, 2008). Signs and symptoms of TB are usually associated with the respiratory system and include coughing, difficulty breathing, bloody sputum, weakness, lethargy, loss of appetite and weight, night sweats, pallor and chest pain.…”
Section: Killing Germs Versus Improving Immunity: What Can Eradicate mentioning
confidence: 99%